(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The Judiciary is experiencing new panoramas in contemporary times, which is due, in sum, to the crisis of representativeness, to its rise as the body that has been responsible for the realization of rights to the population, and for the alteration of judicial profiles for meta-individual demands in reason of the existing mass society. In view of this scenario, this article will analyze, in general, the importance of the Judiciary and public hearings in relation to the exercise of participatory democracy and for the protection of personality rights. And specifically, it will seek to analyze: the role of the Judiciary in contemporary times and the issues related to the crisis of representative democracy; the role of public hearings as an instrument for exercising the right to participation in the judicial sphere and; the importance of personality rights for the protection of the human person and whether public hearings would be relevant in making it effective. As problems to be answered, there are: are public hearings an important instrument for the exercise of participatory democracy within the Judiciary? Are public hearings relevant to the enforcement of personality rights? For that, the hypothetical deductive method and the methodology based on the bibliographic review will be used.